Perceptions of students in different phases of medical education of the educational environment: Universiti Sultan Zainal Abidin - Rahman, Nor Iza A (Adv Med Educ Pract, 2015)
BACKGROUND: The Dundee Ready Education Environment Measure (DREEM) was planned and designed to quantify the educational environment precisely for medical schools and health-related professional schools. DREEM is now considered a valid and reliable tool, which is globally accepted for measuring the medical educational environment. The educational environment encountered by students has an impact on satisfaction with the course of study, perceived sense of well-being, aspirations, and academic achievement. In addition to being measurable, the educational environment can also be changed, thus enhancing the quality of medical education and the environment, and the medical education process. The objective of this study was to assess the educational environment of the Universiti Sultan Zainal Abidin (UniSZA) undergraduate medical program from the students’ perspective. The study expected to explore UniSZA medical students’ overall perceptions, perceptions of learning, teachers, atmosphere, academic self-perception, and social self-perception using the DREEM questionnaire. METHODS: A cross-sectional survey was conducted to study the perceptions of the students toward the educational environment of UniSZA as a new medical school, using the DREEM questionnaire. All medical students of UniSZA from Years I–V enrolled in the Bachelor of Medicine and Bachelor of Surgery programs were the target population (n=270). Therefore, the universal sampling technique was used. The data were analyzed using the SPSS 20 software. This study obtained ethical clearance from the Faculty of Medicine and Health Sciences, UniSZA. RESULTS: A total of 195 out of 270 students responded. Respondents included 31% males and 69% females. The overall DREEM scores were significantly higher (P<0.001) for females than males. CONCLUSION: The medical students at UniSZA showed a positive perception of their educational environment. The new medical faculty, established for only a few years, has achieved an above-average, conducive educational environment for students. Most of the students showed a positive perception for the entire five domains tested in the DREEM survey. Females were consistently satisfied with UniSZA’s educational environment, and self-perception was high, as compared to male undergraduates.